2004
DOI: 10.1590/s1806-83242004000300015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiation mode and filling technique on resin/dentin bonding strength in class I cavities

Abstract: Factors such as light-curing mode, filling technique and cavity configuration may affect the bonding strength to dentin. This study evaluated the effect of irradiation mode and filling technique on resin/dentin bonding strength on the buccal wall of class I cavities in human teeth. Occlusal enamel was removed to expose a flat dentin surface. Occlusal cavities (4 x 3 x 3 mm) were prepared in dentin. The adhesive Single Bond was applied according to the manufacturer's instructions and TPH Spectrum composite resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…Santos, et al 16) , for example, reported that an incremental technique resulted in higher bond strength than a bulk filling technique. On the other hand, other studies on different filling techniques have not detected any difference in bond strength 12,17) which implies that further studies are required in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Santos, et al 16) , for example, reported that an incremental technique resulted in higher bond strength than a bulk filling technique. On the other hand, other studies on different filling techniques have not detected any difference in bond strength 12,17) which implies that further studies are required in this field.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that stresses increased with a lowelasticity modulus base, and it therefore seems appropriate to use high-elasticity base materials. 59 Cusp deformation and recovery under load proved to be influenced by cavity extent and restorative material (composite or porcelain).…”
Section: Comparative Behavior Of Resin Composite and Ceramic Restoratmentioning
confidence: 96%
“…Once again, these findings were product specific. 59 Other authors concluded again that the use of a FRC liner alone did not improve MTBS underneath bulk-filled restorations with a high C-factor, while the presence of fibers or a combination or FRC together with fibers did increase MTBS. 66 Incorporation of glass fibers also showed stable BS values regardless of the C-factor.…”
Section: Microtensile and Shear Testsmentioning
confidence: 98%
See 2 more Smart Citations